Response surface methodology in the optimization of walur (Amorphophallus paeoniifolius var. Sylvestris) starch pregelatinization process - Simon Bambang Widjanarko; Devy Ulandari; Kiki Fibrianto (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
This study aimed to determine the effect of temperature and time of the pregelatinization process on the physical and functional properties of pregelatinized and native walur starch using the central composite design method of response surface methodology (CCD-RSM). Several analyses, including rapid visco analyzer (RVA), scanning electron microscopy (SEM), and X-ray diffraction (XRD), were used to characterize an optimum pregelatinized walur starch (PWS). The optimum conditions for producing PWS were at 87.51oC and 9.71 minutes. The experimental verification data, repeated three times, were not significantly different (P>0.05) from the prediction optimization data generated by the Design Expert Software 7.1.5 Trial Version, which produces PWS with 19.56 ± 0.68 % swelling, 9.87 ± 0.18 % solubility and 835.62 ± 0.84 % water holding capacity (WHC). The result from RVA analysis showed that the pregelatinization process of walur starch increases the peak, final and setback viscosity, peak time, and pasting temperatures but decreases breakdown viscosity. Native walur starch (NWS) had a more crystalline form than PWS on XRD analysis. The SEM analysis revealed that NWS had smooth surface granules compared to PWS granules.